Farmers’ desire to make changes in their agricultural branches in the first wave of COVID-19 pandemic restrictions: The example of Türkiye - Yener Ataseven; Şule Coşkun Cevher; Celal Cevher (Journal of Agricultural Sciences)
The coronavirus pandemic and subsequent protectionary lockdowns have negatively impacted farmers, especially those producing perishable agricultural products worldwide and Türkiye. For this reason, most researchers began to investigate the effects of restrictions on agrarian branches during the sudden shocks of the pandemic. This study was carried out to reveal the farmers’ desire for change in agricultural production branches during the period when coronavirus pandemic restrictions were implemented in Türkiye. A survey study was conducted with broad participation and telephone interviews involving 2125 farmers in different production branches in 22 provinces. Nonlinear Canonical Correlation Analysis was used to analyze variables. According to our analysis results, compared with other agricultural branches, it has been determined that the farmers who do vegetable farming, fruit farming, and livestock farming have a higher desire to change their bare agrarian branches. Approximately half of the farmers interviewed reported difficulties obtaining seeds, fertilizers, and chemicals and providing sufficient labor. Due to these difficulties, 16.5% of the farmers stated that if the first shock effect of the pandemic restrictions continues and this shock effect continues, they will abandon the current main agricultural branches of animal husbandry and vegetable growing. Fruit growing and switch to other farming branches that require less input and labor for agricultural production. For these reasons, policymakers should invest more in market-oriented strategies such as input supply, storage of products, logistics, and processing of manufactured products to maintain the supply chain during pandemic periods. Because these strategies require high costs and the necessary knowledge of post-harvest operations, they are investments that individual farmers cannot afford. Our study revealed that the initial shock effect of the pandemic restrictions in Türkiye had a limited impact on the production of agricultural products. Despite this little impact, 87.3% of farmers stated that their income decreased slightly during this period. We foresee that the restrictions made due to the coronavirus pandemic will affect the planning and social policy in the Turkish economy in the coming years. However, this situation will not change the basic structure of Turkish agricultural production and distribution.